(untitled) (Eurasian Research Bulletin, 2022)
The article discusses the issues of creating an algorithm for controlling the technological parameters of the main gas pipeline - pressure and gas flow using a fuzzy controller, the relevance of solving the problem of creating automatic control systems using intelligent control automation technologies and monitoring technological parameters. For fuzzification by the magnitude of the deviation of pressure and gas flow in the pipeline, the authors presented an algorithm for regulating pressure and flow, and also proposed to use the trapezoidal form of membership functions for three terms and compiled a base of rules. According to the authors, the use of a control algorithm based on fuzzy logic makes it possible to better adapt to the variable operating mode of the gas pipeline and does not require constant selection of the controller coefficients.